Effect of Boswellia serrata extract on Methotrexate induced testicular damage - Arkali, Gozde; Acisu, Tutku Can; Badilli, Nida; Guler-Ekmen, Edanur; Tanyeri, Osman Sedat; Toz, Abdullah; Aksakal, Mesut (Univ Zulia, Facultad Ciencias Veterinarias, 2024)
This study aimed to determine the effect of Boswellia serrata extract on Methotrexate- induced testicular damage by evaluating antioxidant system, reproductive organ weights, some spermatological parametres and serum Testesterone levels. For this purpose, 40 Sprague Dawley rats were divided into 4 groups. 1. Control Group (n=10): No treatment was given for 10 days. 2. B. Serrata Group (n=10): B. Serrata was given by gavage at a dose of 500 mg center dot kg(-1) for 10 days. 3. Methotrexate Group (n=10): Methotrexate was given intraperitoneally as a single dose of 20 mg center dot kg(-1). 4. Methotrexate + B. Serrata Group (n=10): After methotrexate was given intraperitoneally as a single dose of 20 mg center dot kg(-1), 500 mg center dot kg(-1) B. Serrata was given by gavage for 10 days. It was determined that B. Serrata significantly increased serum Testosterone levels (P<0.001), testicular GSH levels (P<0.001), motility of sperm (P<0.001), concentration of sperm (P<0.001), absolute ventral prostate (P<0.001) and absolute seminal vesicles (P<0.05) organ weight in Methotrexate + B. Serrata group. The decrease in testicular MDA levels (P>0.05) and the increase in GSH-Px enzyme activity of testes (P>0.05) and final body weight (P>0.05) were not significant in Methotrexate + B. Serrata group compared to the Methotrexate group. In conclusion, the negative effects of Methotrexate on the male reproductive system can be reduced by administering B. Serrata extract.
Efecto del extracto de Boswellia serrata sobre el daño testicular inducido por Metotrexato
Keywords: Boswellia serrata extract; Methotrexate; testicular injury; sperm; oxidative stress